ANALISIS RESIKO NILAI EKONOMI DAN PRODUKSI USAHATANI PADI SAWAH DI DESA PUNDEN REJO KECAMATAN TANJUNG MORAWA - Tanjung, Ade Firmansyah; Kembaren, Emmia Tambarta; Fadli, Fadli; Barmawi, Barmawi; Nurhajijah, Nurhajijah (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2023)
Realizing the welfare of farmers starts with increasing the economic value and feasibility of the income received in accordance with the needs of the farmer's household. The hope is that the economic value obtained from farming is still at the limit of a low level of farming risk. Implementation of the research location in Punden Rejo Village. For primary data processing, questionnaires and interviews were conducted with 30 farmers. For the determination of respondents conducted by disproportionate stratified random sampling method. To calculate the level of risk of economic value of farming can use variance analysis (Variance) and standard deviation (standard deviation). After calculating the value of variance and standard deviation, then the next step is to calculate the coefficient of variation (CV). Based on the results of research conducted from data from interviews and observations at the research location, for risk analysis of the economic value of farming based on the calculation of the coefficient of variation (CV) less than 0.5 (0.23 < 0.5) and risk analysis of production value based on the calculation of the coefficient of variation (CV) less than 0.5 (0.22 < 0.5).